Murine Typhus: An Important Consideration for the Nonspecific Febrile Illness - Gurjot Basra; Megan A. Berman; Lucas S. Blanton (Case Reports in Medicine)
Murine typhus is a widely distributed flea-borne infection caused by Rickettsia typhi. Symptoms of murine typhus are nonspecific and mimic a variety of other infectious diseases. We herein report a case of murine typhus in an area where the broad use of DDT in the mid-20th century has now made it a rare disease. The patient described presented with headache, fever, and a faint macular rash. Initial laboratory studies revealed a slight transaminase elevation. Further questioning revealed exposure to opossums, prompting the consideration of murine typhus as a diagnosis. Although typhus group antibodies were not present during the patient’s acute illness, empiric therapy with doxycycline was initiated, and the patient defervesced. One month after convalescence, the patient returned to clinic with serum that contained typhus group antibodies with an IgG titer of 1 : 1024. Murine typhus is an important consideration during the workup of a patient with a nonspecific febrile illness. Exposure to reservoir hosts and the flea vector place humans at risk for this disease. Clinician recognition of this entity is required for diagnosis and effective therapy.